Kiprah Dakwah Al-Washliyah di Tatar Sunda - Acep Aripudin (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2022)
Alwashliyah is a da'wah organization with a different culture from the society in which the organization was born. This article aims to reveal the map of Aljamiyatul Washliyah's da'wah and other socio-religious organizations in West Java. The data to inform the theme of Alwashliyah da'wah is qualitative. Meanwhile, the socio-historical approach is used as an analytical tool and comparative to sharpen the map of the da'wah movement further. As for Alwashliyah's da'wah activities in West Java, namely: First, it was started in 1956 in the northern region of West Java through educational approaches and social activities; second, the da'wah method is carried out through tabligh, tadbir, tathwir. Alwashliyah da'wah in West Java is still concentrated in education and religious studies. Just like the da'wah of similar organizations. So that competition occurs in carrying out da'wah because the targets and forms are identical, impacting the inclusion of internal religious sentiments.